A Comparative Study Evaluating Muslim-Friendly Compliant Standards: Sultan Abdul Aziz Shah Airport Vs. Yogyakarta International Airport (YIA) - Siti Hawa Radin Eksan; Haliyana Tonot; Mohd Fadhli Ab Rahman; Achmad Fajaruddin; Andika Rendra Bimantara (Penerbit USIM, 2025)
International Halal Management Conference (IHMC) : “Empowering Halal Industry Towards Globalization” / Editor :-Farah Laili Muda @ Ismail, Nur Ainna Ramli & Anita Ismail Organized by Faculty of Economics & Muamalat, Universiti Sains Islam Malaysia 9 September 2025